Contusions of the abdomen in childhood: Analysis of 229 observations - de Torres, Editta Falco (Cirugía del Uruguay, 1978)
229 cases of closed abdominal injuries in children under 14 years of age, are analyzed. Renal lesions are the most frequent ( 19 % ) . In 47 % of cases no visceral lesions were found. The remaining 44 % were operated and the following lesions were found: Rupture of liver 13. 9 % ; of spleen 13 %; retroperitonear hematoma 5 % and hollow víscera lesions 2 %. Extra-abdominal lesions accounted far 33 %. Overall death-rate was 2. 6 % .